Stability analysis of nonlinear convective boundary layer flow on a shrinking surface in the presence of viscous dissipation - Rehman, Ali; Zeb, Muhammad; Waheed, Asif; İnç, Mustafa; Yagoob, Budur; Jan, Rashid (World Scientific Publ Co Pte Ltd, 2024)
This study investigates analytically the stability analysis of a nonlinear convective boundary layer (BL) flow of the nanofluids GO-EG and GO-W on a shrinking surface in the presence of a magnetic field and viscous dissipation. We provide a second-order nonlinear ordinary differential equation (NODE) for temperature distribution (TD) and a third-order NODE for velocity profile (VP) coupling based on the thermophysical characteristics of the base fluid and nanofluid as well as similarity transformations (STs) in the fundamental governing equations of momentum and energy. The analytical method HAM is used to answer the equations that have been gathered. In many different industries, such as manufacturing, automotive, microelectronics, and defense, cooling of various types of equipment and devices has very important challenges. To fulfill the demands of the engineering and industrial industries, it is hoped that this issue would significantly improve the heat transformation ratio.
Keywords: Stability analysis; shrinking surface; nanoparticle; nanofluidics; coupled equations numerical method